2019
DOI: 10.1002/ange.201913895
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydride Reduction of Polycyclic Aromatic Hydrocarbons

Abstract: A molecular calcium hydride effects the two electron reduction of polyaromatic hydrocarbons, including naphthalene (E0=−3.1 V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Although an exchange spectroscopy (EXSY) NMR experiment demonstrated that 2 and 2' are in equilibrium at room temperature, attempts to quantify this process by variable temperature 1 H NMR studies were frustrated by the competitive redistribution to the homoleptic ytterbium complex, [(BDI Dipp ) 2 Yb] 36 , and facile Yb-H/D exchange with the deuterobenzene solvent. In this latter regard, the signal associated with the hydride ligand of 2 was observed to decrease if left in benzene-d 6 for extended periods of time (>6 h), concomitant with the formation of a new signal in the 2 H NMR spectrum centred at 7.92 ppm, which was assigned as the ytterbium deuteride [BDI Dipp YbD] 2 , 2-d 7,37 .…”
Section: Resultsmentioning
confidence: 99%
“…Although an exchange spectroscopy (EXSY) NMR experiment demonstrated that 2 and 2' are in equilibrium at room temperature, attempts to quantify this process by variable temperature 1 H NMR studies were frustrated by the competitive redistribution to the homoleptic ytterbium complex, [(BDI Dipp ) 2 Yb] 36 , and facile Yb-H/D exchange with the deuterobenzene solvent. In this latter regard, the signal associated with the hydride ligand of 2 was observed to decrease if left in benzene-d 6 for extended periods of time (>6 h), concomitant with the formation of a new signal in the 2 H NMR spectrum centred at 7.92 ppm, which was assigned as the ytterbium deuteride [BDI Dipp YbD] 2 , 2-d 7,37 .…”
Section: Resultsmentioning
confidence: 99%